Magnetodynamics in exchange coupled composite magnets - Richa Bhardwaj; Antonio Caretta; Simone Laterza; Gabriele Coltrioli; Francesco Cautero; Amardeep Bharti; Kapil Dev; Pietro Parisse; Cinzia Di Giorgio; Subramanian Annapoorni; Asokan Kandasami; Marco Malvestuto (Scientific Reports)
Abstract Tailoring magnetization using all-optical methods in exchange-coupled composite magnets holds significant scientific potential for advancing ultrafast magneto-optic devices. Here, we investigate the femtosecond laser-activated magnetization dynamics in FeNi/FePt composites using time-resolved magneto-optical Kerr effect (tr-MOKE) spectroscopy across the both visible and extreme ultraviolet spectral ranges. Observations from visible tr-MOKE reveal ultrafast demagnetization and an initial magnetization reorientation, characterized by a transient increase in the in-plane magnetization vector occurring on timescales shorter than 500 fs. Core-resonant tr-MOKE at Ni, Fe $$\hbox {M}_{2,3}$$ and Pt $$\hbox {N}_{6,7}$$ -edge provide an element-specific contribution to the magnetodynamics. We infer that the sub picosecond magnetodynamics arises from the interplay between spin disordering and the dynamic nature of interlayer exchange coupling between FeNi and FePt in FeNi/FePt.